KUALITAS ORGANOLEPTIK DAGING SAPI BALI YANG DILAYUKAN DENGAN LAMA WAKTU YANG BERBEDA - SINAGA M. O. A.; N. L. P. SRIYANI; I G. SUARTA (Majalah Ilmiah Peternakan, 2021)
The objective of the research was to know the optimal length time of bali beef aging in order to produce the best quality of its organoleptic. Analyses used was Non Parametric Kruskal Wallis. If the results significantly different, it will be continued to Mann Whitney analyses. Treatments used were fresh beef without aging (P0), aging beef for 6 hours (P1), aging beef for 8 hours (P2) and aging beef for 10 hours (P3) on the same room temperature (28-29oC). Results showed that beef texture score decreased significantly different (P<0.05) from P0 to P3. The highest beef aromatic and colour of P0 significantly different (P<0.05) compare to the P1, P2, and P3. The tenderness of the P3 was the highest with score for 3.92 and significantly different (P< 0.05) than the P0, P1 and P2. The highest taste was the P2 with score for 3.46 significant different (P<0.05) than the P0, P1 and P3. The highest score of the beef acceptance totally was 4.08 of P1 significantly different (P<0.05) compare to the P0, P2, and P3. It can be concluded that the length time of bali beef aging could affect beef organoleptic and the optimal time to produce the best quality organoleptic of the beef is 6 hours.